Biosynthetic Pathway of psi, psi-Carotene from Streptomyces sp. VITGV38 (MCC 4869) - Pattapulavar, Veilumuthu; Ramanujam, Sathiyabama; Sekaran, Manoj; Chandrasekaran, Rajasekaran; Panchal, Shweta; Christopher, John Godwin (Frontiers in Microbiology, 2025)
IntroductionEndophytic Streptomyces play a crucial role in plant-microbe interactions, often exhibiting beneficial biological activities, including the production of bioactive secondary metabolites. This study aimed to characterize the carotene biosynthetic pathway of a newly discovered Streptomyces sp. VITGV38, isolated from tomato (Lycopersicon esculentum).MethodsThe strain (Streptomyces sp. VITGV38, MCC4869) was cultured in starch casein broth, and its metabolite profile was analyzed using Gas Chromatography-Mass Spectrometry (GC-MS). Whole-genome sequencing was performed using the Illumina platform, and the biosynthetic gene clusters (BGCs) were identified using antiSMASH.ResultsMetabolite analysis revealed the presence of pigmented compounds, including psi, psi-carotene, detected at a retention time of 25.094, constituting 1.26% of the crude extract. Whole-genome sequencing uncovered an 8.27 Mb genome encoding 26 distinct secondary metabolite biosynthetic gene clusters. Notably, scaffold 26.3 was identified as a terpene biosynthetic cluster, accounting for 62% of the total secondary metabolite content and associated with carotenoid and β-carotene production.DiscussionThese findings highlight the biotechnological potential of Streptomyces sp. VITGV38 for sustainable microbial production of carotenoids, offering an eco-friendly alternative to synthetic pigments. This study provides valuable insights into microbial carotenoid biosynthesis and its potential industrial applications.